Performance of Disc and Chisel Ploughs and their Effects on Some Soil Physical Properties (University of Khartoum Journal of Agricultural Sciences, 2023)
A study was carried out at the University of KhartoumDemonstration Farm in (2007), to study the performance of two tillageimplements: (disc and chisel plough) and their effect on some soilphysical properties. The results showed that the higher values of boththeoretical and effective field capacities were recorded by chisel plough(1.23 ha/hr and 0.90 ha/hr) as compared to disc plough (0.63 ha/hr and0.50 ha/hr). The higher field efficiency was recorded by disc plough(79.37%) as compared to the chisel plough (73.4%). The fuel consumedwhen using the disc plough was (10.60 l/ha) less than that consumed bythe chisel (13.47 l/ha). Tractor wheel slippages ware found to be 10.92%.and 14.1%. The result also showed that both ploughs decreased the soilbulk density values from 1.54 g/cm3 to 1.51 and 1.49 g/cm3 by disc andchisel plough respectively. Particle density was not affected (P > 0.05) byboth implements . The soil porosity values were also increased for bothimplements. The soil moisture content recorded in two depths 0-15 and15-30 cm were higher for chisel plough (6.53% and 6.9%) as compared todisc plough which recorded 6.3% and 6.5% respectively. The infiltrationrate obtained by the disc plough was 22.2 cm/hr while that of chiselplough was (20.1 cm/hr)
Keywords: Disc plough; chisel plough; soil physical properties.